Female masculinities and gender wars : the politics of sex - Mackay, Finn (New York : I.B. Tauris, 2021)
"Thoughtful and often moving." Gaby Hinsliff, The Guardian. Female Masculinities and the Gender Wars provides important theoretical background and context to the 'gender wars' or 'TERF wars'- the fracture at the forefront of the LGBTQ international conversation. Using queer and female masculinities as a lens, Finn Mackay investigates the current generational shift that is refusing the previous assumed fixity of sex, gender and sexual identity. Transgender and trans rights movements are currently experiencing political backlash from within certain lesbian and lesbian feminist groups, resulting in a situation in which these two minority communities are frequently pitted against one another or perceived as diametrically opposed. Uniquely, Finn Mackay approaches this debate through the context of female masculinity, butch and transmasculine lesbian masculinities. There has been increasing interest in the study of masculinity, influenced by a popular discourse around so-called'toxic masculinity', the rise of men's rights activism and theory and critical work on Trump's America and the Me Too movement. An increasingly important topic in political science and sociological academia, this book aims to break new ground in the discussion of the politics of gender and identity
Includes bibliographical references and index.
In English.
Keywords: Sociology; -- Lesbian studies; Sex role -- Gender identity; Social Science -- Gender Studies